An ovarian bioreactor for in vitro culture of the whole bovine ovary: a preliminary report. Issue 1 (December 2016) - Zanotelli, Matthew; Henningsen, Joseph; Hopkins, Patrick; Dederich, Aaron; Herman, Tessa; Puccinelli, Tracy; Salih, Sana
Abstract Background Improved cancer therapeutics and enhanced cancer survivorship have emphasized the severe long-term side effects of chemotherapy. Specifically, studies have linked many chemotherapy agents with primary ovarian insufficiency, although an exact insult model has not yet been determined. To investigate and ultimately solve this problem, a novel device for extended study of mammalian ovaries in vitro was developed. Methods A bioreactor was fabricated for bovine ovarian culture that provides intravascular delivery of media to the ovary through isolation and cannulation of a main ovarian artery branch. Whole ovaries were cultured in vitro using three methods: (1) continuously supplied fresh culture media, (2) recirculated culture media, or (3) continuously supplied fresh culture media supplemented with 500 nM doxorubicin for 24 or 48 h. TUNEL assay was used to assess apoptotic cell percentages in the three groups as compared to uncultured baseline ovaries. Results The ovary culture method was shown to maintain cell viability by effectively delivering nutrient-enriched pH-balanced media at a constant flow rate. Lower apoptosis observed in ovaries cultured in continuously supplied fresh culture media illustrates that this culture device and method are the first to sustain whole bovine ovary viability for 48 h. Meanwhile, the increase in the percentage of cell apoptosis with doxorubicin treatment indicates that the device can provide an alternative model for testing chemotherapy and chemoprotection treatments to prevent primary ovarian insufficiency in cancer patients. Conclusions An ovarian bioreactor with consistent culture media flow through an ovarian vasculature-assisted approach maintains short-term whole bovine ovary viability.